Pengalaman Komunikasi Lintas Budaya Peserta Pertukaran Mahasiswa Indonesia Di Korea Selatan Studi Fenomenologi Mengenai Pengalaman Komunikasi Peserta Pertukaran Mahasiswa Indonesia di Ajou University, Korea Selatan Periode Musim Gugur 2022 - Afifa Afra (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research is to determine the motives of Indonesian exchange participants in carrying out cross-cultural communication during their student exchange period in South Korea, their cross-cultural communication experiences during student exchange period in South Korea, as well as the meaning of cross-cultural communication received from their communication experiences in South Korea.The results of this research show that the motives of Indonesian student exchange participants in carrying out student exchange in South Korea are divided into two, namely because-of-motive which came from stereotypes about South Korea and in-order-to-motive which came from their interest in South Korean culture, education, desire to expand friendships, and deepening or gaining Korean language skills. Then, it was revealed that Indonesian students experienced culture shock in several stages; initial euphoria, irritation and hostility, gradual adjustment, and acceptance and integration, with language being the most common cross-cultural communication barrier that causes negative communication experiences in both academic and non-academic environments. In interpreting their communication experiences, Indonesian exchange students show that they find differences and similarities in communication styles between South Korea and Indonesia. Through understanding the differences and similarities in communication styles, they can find solutions to overcome communication barriers that occur, namely through building friendships and deepening language skills. The impacts that arise on students include becoming more open-minded individuals, respecting other people's privacy and the emergence of new good habits in each informant.